Community Empowerment and MSMEs Quality Improvement Through Tandes Village Digital Assistance - Amalia Ramadhany, Ekik Setyo; Khoiro, Muhimmatul (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2023)
Current technological developments have shown extraordinary progress. Many things from the life sector have used the existence of technology itself. The development of advanced technology is very rapid, one of which is in the economic sector, namely digital marketing. Business actors of Micro, Small and Medium Enterprises (MSMEs) are one of the supporters of the Indonesian state economy and regional economic strength which are incessantly utilizing digital marketing in promoting their businesses. For example, in the Tandes Village area, most residents have their own MSME products. However, residents there have not been able to take advantage of existing digital marketing technology in developing their businesses. For this reason, digital marketing socialization and digital marketing training and product marketing are being held so that residents around Tandes can make good use of digital marketing technology so that the businesses they create are expected to grow more rapidly because of this digital marketing technology.